Validitas E-Modul Berbasis Website pada Submateri Klasifikasi Makhluk Hidup untuk Meningkatkan Kemampuan Berpikir Kritis - Noviani, Sulis; Nuraida, Dede (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Suboptimal science learning results in low learning outcomes. This is caused by several factors, such as less interesting teaching materials, and not being able to improve students' critical thinking skills. This study aims to develop a website-based E-Module product on the sub-material of classification of living things to improve students' critical thinking skills. The research method used is development research with a 4D model. The research instrument in the form of an expert validation sheet is used to measure the feasibility of the E-Module. The types of data collected include qualitative data (comments and suggestions) and quantitative data (validation assessment scores). The data analysis technique is descriptive qualitative. The results of the study show the percentage of feasibility in various aspects, namely the feasibility of content/material of 89.5%, depth of material 90%, breadth of material 90.3%, language 89.375%, systematic presentation 90.714%, and graphics 90.384%. The average percentage of all aspects assessed by the validator is 90.1%. Thus, it can be concluded that the website-based e-module on the classification of living things subtopic is highly valid and suitable for improving students' critical thinking skills.